Myosin light-chain kinase of smooth muscle stimulates myosin ATPase activity without phosphorylating myosin light chain - Ye, Li-Hong (The National Academy of Sciences, 1999)
Myosin light-chain kinase (MLCK) of smooth muscle is multifunctional, being composed of N-terminal actin-binding domain, central kinase domain, and C-terminal myosin-binding domain. The kinase domain is the best characterized; this domain activates the interaction of smooth-muscle myosin with actin by phosphorylating the myosin light chain. We have recently shown that the Met-1–Pro-41 sequence of MLCK binds to actin to inhibit this interaction. However, it is not known whether the myosin-binding domain modifies the actin–myosin interaction. We designed MLCK⋅cDNA to overexpress the Asp-777–Glu-972 sequence in Escherichia coli. The purified Asp-777–Glu-972 fragment, although devoid of the kinase activity, exerted a stimulatory effect on the ATPase activity of dephosphorylated myosin (V(max) = 7.36 ± 0.44-fold, K(m) = 1.06 ± 0.20 μM, n = 4). When the N-terminal 39 residues of the fragment were deleted from the fragment, the resultant fragment, Met-816–Glu-972, lost the stimulatory activity. We synthesized the Ala-777–Ser-815 peptide that was deleted from the fragment and confirmed its stimulatory effect of the peptide (V(max) = 3.03 ± 0.22-fold, K(m) = 6.93 ± 1.61 μM, n = 3). When this peptide was further divided into Asp-777–Met-795 and Ala-796–Ser-815 peptides, the stimulatory activity was found in the latter. We confirmed that the myosin phosphorylation did not occur during the experiments with the above fragments and peptides. Therefore, we suggest that phosphorylation is not obligatory for smooth-muscle myosin not to be active.